Changing the channel: A qualitative analysis of an innovative video intervention to explore resident attitudes towards interprofessional collaboration on a Geriatric Medicine Unit - Whitney, Krista; Peck, Vanessa; Huang, Allen R; Park, Junghyun; Menard, Prudy; MacDonald, Jason; Spilg, Edward; Khoury, Lara (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2023)
Background: Medical learners develop a more positive attitude toward Interprofessional Collaboration (IPC) following Interprofessional Education (IPE) programs. However, IPE is not standardized and the most effective teaching tool is unclear. The purpose of our study was to develop an IPE teaching tool for medical residents during an inpatient geriatric medicine rotation at an academic hospital, evaluate and explore the impact of the program on resident attitudes towards teamwork, and identify barriers and facilitators to interprofessional collaboration.Methods: An innovative video was developed which simulated a common IPC scenario. Near the start of the rotation, learners watched the video then participated in a facilitated discussion around principles of IPE, using the Canadian Interprofessional Health Collaborative (CIHC) framework, which highlights interprofessional communication, patient-centered care, role clarification, team functioning, collaborative leadership, and interprofessional conflict resolution. At the end of their four-week rotation, focus groups were conducted to explore resident attitudes towards IPE. The Theoretical Domain Framework (TDF) was used for qualitative analysis.Results: Data from 23 participants in five focus groups were analyzed using the TDF framework. Residents were able to identify barriers and facilitators to IPC in five TDF domains: environmental context and resources, social/professional role and identity, knowledge, social influences and skills. Their observations correlated with the CIHC framework.Conclusion: The use of a scripted video and facilitated group discussion gave insights into residents’ attitudes, perceived barriers and facilitators towards IPC on a geriatric medicine unit. Future research could explore the use of this video intervention in other hospital services where team-based care is important